Oxygenation by Hollow Plunging Water Jet - Deswal, Surinder (Journal of the Institute of Engineering, 2009)
Oxygenation by a plunging water jet is a more attractive way to effect oxygen-transfer than conventional oxygenation systems. A lot of work has been reported on the oxygen-transfer by plunging water jets. However, few studies have been carried out on hollow plunging jet. In this paper, volumetric oxygen-transfer coefficient and oxygen-transfer efficiency has been studied experimentally for hollow plunging jet in a pool of water for different thicknesses of jets. This research suggests that the volumetric oxygen-transfer coefficient and oxygen-transfer efficiency of the hollow plunging jet for air-water system are competitive with other types of aeration systems. Further, relationships of volumetric oxygen-transfer coefficient with jet power per unit volume and jet parameters are also proposed. The suggested relationships predict the volumetric oxygen-transfer coefficient for hollow plunging water jet within a scatter of ±15%. Key words: hollow plunging jet, oxygenation, volumetric oxygen-transfer coefficient, oxygentransfer efficiency, jet power. Journal of the Institute of Engineering, Vol. 7, No. 1, 2009 July pp. 40-47 doi: 10.3126/jie.v7i1.2061